Metabolic reprograming shapes neutrophil functions in severe COVID‐19. Issue 3 (24th December 2021) - Borella, Rebecca; De Biasi, Sara; Paolini, Annamaria; Boraldi, Federica; Lo Tartaro, Domenico; Mattioli, Marco; Fidanza, Lucia; Neroni, Anita; Caro‐Maldonado, Alfredo; Meschiari, Marianna; Franceschini, Erica; Quaglino, Daniela; et al.
Abstract: To better understand the mechanisms at the basis of neutrophil functions during SARS‐CoV‐2, we studied patients with severe COVID‐19 pneumonia. They had high blood proportion of degranulated neutrophils and elevated plasma levels of myeloperoxidase (MPO), elastase, and MPO‐DNA complexes, which are typical markers of neutrophil extracellular traps (NET). Their neutrophils display dysfunctional mitochondria, defective oxidative burst, increased glycolysis, glycogen accumulation in the cytoplasm, and increase glycogenolysis. Hypoxia‐inducible factor 1α (ΗΙF‐1α) is stabilized in such cells, and it controls the level of glycogen phosphorylase L (PYGL), a key enzyme in glycogenolysis. Inhibiting PYGL abolishes the ability of neutrophils to produce NET. Patients displayed significant increases of plasma levels of molecules involved in the regulation of neutrophils' function including CCL2, CXCL10, CCL20, IL‐18, IL‐3, IL‐6, G‐CSF, GM‐CSF, IFN‐γ. Our data suggest that metabolic remodelling is vital for the formation of NET and for boosting neutrophil inflammatory response, thus, suggesting that modulating ΗΙF‐1α or PYGL could represent a novel approach for innovative therapies. Abstract : Patients with severe COVID‐19 exhibit changes in several granulocytes' subsets. High levels of degranulated neutrophils are present together with elevated plasma levels of MPO‐DNA complexes and proinflammatory cytokines. Neutrophils display increased glycolysis, increased HIF‐1α, huge amount of glycogen in cytoplasm, and increased glycogenolysis, which has a role in NET formation.